Sejarah Pemikiran Ekonomi Klasik - Kholimah; Agung; Gita Oktavia Rosita; Muhammad Usman Ariffianto; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine the history of classical economic thought. This research is library research with a qualititative approach. The data sources used in this research come from various literature journal articles that are relevant to the research topic. The data analysis method used is content analysis of the literature sources used in the research. The results of this research is classical economics is generally regarded as the first modern school in the history of economic thought. The main thinkers and developers of this school include Adam Smith, Jean Baptiste Say, David Ricardo, Thomas Malthus and John Stuart Mill. The classical school emerged in the late 18th and early 19th centuries during the industrial revolution. The idea espoused by the classical school that output and price equilibrium can only be achieved if the economy is at full employment can only be achieved through the operation of free market mechanisms. The Wealth of Nations had a significant impact since it contributed to the systematic and independent development of economics as a subject. The main problem of classical economics is a problem consisting of three main problems of classical economic theory, namely production, distribution, and consumption.